Pengaruh Pemberian Zat Warna Alami dari Kayu Secang (Caesalpinia Sappan L) dan Umbi Buah Bit (Beta Vulgaris L) terhadap Evaluasi Sediaan lip tint - Denia Pratiwi; Fauziah Fauziah (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Lip tint is one of the liquid lip cosmetic preparations used to color lips with natural colors. This study aims to see the effect of adding natural dyes to secang wood (Caesalpinia Sappan L) and beetroot (Beta Vulgaris L) on the evaluation of preparations in terms of homogeneity, pH test (SNI No 16-4769-1998), smearability test, irritation & preference test, and stability test. Lip tint preparations were made into three concentrations, namely by the ratio of secang wood and beetroot tubers in each formula, namely F1 (25%: 25%), F2 (35%: 15%), F3 (10%: 40%) successively. The results obtained from this study were lip tint preparations that were not homogeneous on F1 and F2, had good abrasive power on all three formulas, did not irritate the skin, and the pH obtained did not meet the requirements of the pH test, and F2 was a preparation that was liked by many panelists, whereas in the stability test at week 2 all formulas showed changes in color and consistency indicating that the preparation was unstable.